An approach to acute severe ulcerative colitis. (3rd October 2019) - Sedano, Rocío; Quera, Rodrigo; Simian, Daniela; Yarur, Andres J.
ABSTRACT: Introduction : Despite the introduction of novel therapies and treatment strategies for ulcerative colitis (UC), many patients develop acute, severe episodes, warranting prompt care and aggressive management. There is a significant unmet need to improve outcomes in these patients. Clinicians must be able to identify those that will have worse prognosis and plan an aggressive therapy with an early/proactive adjustments in management if needed. Areas covered : The aim of this review is to evaluate the most recent evidence on the assessment and management of patients with acute severe ulcerative colitis. We searched the mainstream literature search engines for the most recent evidence on diagnosis and management of acute UC. Expert Opinion : The approach to patients with severe UC includes clinical and endoscopic assessment of disease severity and ruling out over-infections. While intravenous corticosteroids remain the first line therapy for acute severe colitis, many patients do not respond and require escalation to calcineurin inhibitors or infliximab, and may ultimately require colectomy. Even though several novel therapies are available or in development, their role in acute severe episodes of colitis is unknown.